Metastatic melanoma posing as a pelvic mass - Alexsaundra Zywicki; Naixin Zhang; Olivia Sagan; Richard Moore; Rachael Rowswell-Turner; Cynthia Angel; Brent DuBeshter; Numbereye Numbere; Ashlee Smith (Elsevier, 2023)
Pelvic metastasis of melanoma is extremely rare and may pose a diagnostic challenge. We present a case report of a female with a history of colon cancer who underwent exploratory surgery for a pelvic mass that was suspicious for ovarian malignancy. Pathology was consistent with both recurrent colon cancer as well as synchronous newly diagnosed metastatic melanoma.